The Cinema of Hong Kong history, arts, identity - Fu, Poshek 1955-; Desser, David (Cambridge University Press, 2000)
The Cinema of Hong Kong examines one of the most popular, dynamic, and important cinema traditions in the history of film. Providing an overview of major directors, genres, and stars, from its origins to the present, this volume examines Hong Kong cinema in historical, transnational, cultural and political contexts. Individual chapters focus on Hong Kong cinema before and during World War II, the cinema of the turbulent 1960s, its rise to world prominence in the 1970s, its reception in the United States, and the revival of Cantonese cinema, among topics. Including contributions from a diverse roster of scholars, archivists, and film programmers, the book provides a wealth of new information and new conceptual framework, enabling a greater appreciation of the variety, range and depth of Hong Kong film